Theoretical ecology : principles and applications - May, Robert M.; McLean, Angela R. (New Delhi : Open University Press, 2007)
The third edition of May's influential text will first provide a comprehensive overview of the basic principles that underpin the structure, function and dynamics of individual populations and communities, whilst later chapters will then deal with applications.
Includes bibliographical references and index.
Keywords: Ecology; Electronic books